Organizational Culture in Improving Teacher Performance in Support of SDG 4 (Quality Education) - Sulastri Sulastri; Syahril Syahril; Nelfia Adi; Yulianto Santoso; Lutfiani Lutfiani; Sari Febrianti; Widiawati Widiawati; Hendri Budi Utama; Hardianto Hardianto (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2027)
Objective: To describe the organizational culture of public senior high schools in West Pasaman Regency and examine its potential contribution to improving teacher performance. Organizational culture is assessed through three indicators: collaboration, trust, and honesty. The study also positions a supportive school culture as an institutional mechanism for advancing Sustainable Development Goal 4, particularly the provision of quality education through effective and professional teaching practices. Method: A descriptive quantitative design was employed. The population comprised 359 teachers from public senior high schools in West Pasaman Regency. A sample of 98 teachers was selected through proportional stratified random sampling. Data were collected using a Likert-scale questionnaire distributed through Google Forms. The collected data were analyzed using mean scores and percentage calculations to determine the achievement level of each organizational culture indicator. Results: The findings indicate that organizational culture was generally classified in the good category, with an overall achievement rate of 80.35%. Trust obtained the highest achievement rate at 85.48%, followed by honesty at 83.31% and collaboration at 83.25%. These results demonstrate that positive cultural values have been established across the participating schools, although further improvement remains necessary to optimize their contribution to teacher performance. Novelty: To provide empirical evidence regarding organizational culture in public senior high schools in West Pasaman Regency by integrating collaboration, trust, and honesty within a single descriptive framework. It further highlights organizational culture as a school-level foundation for strengthening teacher performance and supporting SDG 4 through sustainable improvements in educational quality.